1995
DOI: 10.1111/j.1365-2141.1995.tb08364.x
|View full text |Cite
|
Sign up to set email alerts
|

Interferon alfa‐2b versus no maintenance therapy during the plateau phase in multiple myeloma: a randomized study

Abstract: This clinical trial was designed to investigate if maintenance therapy with alfa-interferon could prolong the plateau phase in patients with multiple myeloma. In addition, the tolerability of interferon treatment and its effect on survival were evaluated. From September 1987 to September 1989 a total of 314 patients were accrued to a multi-institutional randomized clinical trial. All patients entered into the protocol received standard melphalan-prednisone (MP) induction therapy. Response was noted in 184 (59%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
1
2

Year Published

1997
1997
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 15 publications
0
48
1
2
Order By: Relevance
“…This finding is in agreement with most studies on IFN maintenance in MM. [20][21][22][23] However, it is worth mentioning that in our study the median response duration was prolonged for only 6 months in the IFN arm compared with the observation group and that the statistical significance is borderline. In this regard, the prolongation of response in studies showing a significant benefit from IFN maintenance has also been modest, with differences in median response duration ranging from 5 to 12 months.…”
Section: Figurecontrasting
confidence: 64%
See 3 more Smart Citations
“…This finding is in agreement with most studies on IFN maintenance in MM. [20][21][22][23] However, it is worth mentioning that in our study the median response duration was prolonged for only 6 months in the IFN arm compared with the observation group and that the statistical significance is borderline. In this regard, the prolongation of response in studies showing a significant benefit from IFN maintenance has also been modest, with differences in median response duration ranging from 5 to 12 months.…”
Section: Figurecontrasting
confidence: 64%
“…In this regard, the prolongation of response in studies showing a significant benefit from IFN maintenance has also been modest, with differences in median response duration ranging from 5 to 12 months. [20][21][22][23] In contrast to these observations, other trials have failed to show a significant advantage in response duration for IFN maintenance. 8,[24][25][26] Regarding overall survival, most available data, including our own study, suggest that there are no significant differences in survival from the time of randomization in patients maintained with IFN as compared to the observation group.…”
Section: Figurementioning
confidence: 96%
See 2 more Smart Citations
“…Following conventional chemotherapy, randomized studies indicate that IFNa prolongs remission duration by 5-12 months. 14,[17][18][19] These trials also found a minimal or no survival advantage in the IFNa-treated patients. Plateau phase duration in those patients treated with IFNa ranged from 14 to 16 months.…”
Section: Discussionmentioning
confidence: 98%